2022
DOI: 10.33116/ije.v5i1.110
|View full text |Cite
|
Sign up to set email alerts
|

Energy Storage Applications to Address the Challenges of Solar PV and Wind Penetration in Indonesia: A Preliminary Study

Abstract: Indonesia intends to increase the renewable energy ratio to at least 23% from the energy mix generated by 2025. This target is also in line with the Paris Agreement that Indonesia ratified in October 2016. However, renewable energy capacity has not been significant, as 11.38% of the total on-grid power capacity (MEMR, 2021). More than 90% of renewable comes from hydropower and geothermal, and only a limited capacity comes from wind and solar energy. On the other hand, wind and solar energy potential are enormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…As ASEAN countries are gradually increasing renewable energy generation based on abundant sources of renewable energy such as solar and wind energy, research on the application of renewable energy and the BESS integrated system is also in its initial stage. Umam et al [31] compared the economic feasibility of solar PV alone, the solar PV and lithium-ion BESS integrated system, and pumped hydro energy storage (PHES) in Indonesia and found that the economic feasibility of the solar PV and BESS integrated system is currently the lowest. Erlina et al [34] simulated the applicability of a wind farm and the BESS integrated system using lithium-ion batteries on Buton Island, Baubau, Southeast Sulawesi, Indonesia, and found that this system achieved load leveling and peak shaving effects.…”
Section: Literature Related To the Bess And Renewable Energy Integrat...mentioning
confidence: 99%
See 1 more Smart Citation
“…As ASEAN countries are gradually increasing renewable energy generation based on abundant sources of renewable energy such as solar and wind energy, research on the application of renewable energy and the BESS integrated system is also in its initial stage. Umam et al [31] compared the economic feasibility of solar PV alone, the solar PV and lithium-ion BESS integrated system, and pumped hydro energy storage (PHES) in Indonesia and found that the economic feasibility of the solar PV and BESS integrated system is currently the lowest. Erlina et al [34] simulated the applicability of a wind farm and the BESS integrated system using lithium-ion batteries on Buton Island, Baubau, Southeast Sulawesi, Indonesia, and found that this system achieved load leveling and peak shaving effects.…”
Section: Literature Related To the Bess And Renewable Energy Integrat...mentioning
confidence: 99%
“…Moreover, the energy rating and lifetime of the battery consider the load and PV-supply characteristics of the grid-connected transformer [15]. The lifetime of RBESSs used by previous studies for solar PV systems ranged from 5-20 years [28,30,31,33,34]. In the present study, the RBESS lifetime was set as 10 years; thus, it would need to be replaced every 10 years (two times in total) during the entire operation period of the proposed system.…”
Section: Technical and Financial Specifications Of The Solar Pv Systemmentioning
confidence: 99%
“…In the case of Indonesia, offshore wind energy research has not made significant progress because the majority is still in the form of potential studies in several areas, but those will make good progress for the development [10]- [16]. Although this industry is very promising, many challenges must be resolved such as the large costs incurred for its study, development, and construction [17]. Primary data become a challenge in offshore wind energy development because of its high costs for maritime countries like Indonesia.…”
Section: Introductionmentioning
confidence: 99%